E-064 Adjunctive Stent are Not Flow Diverters: A Computational Flow Dynamics Study Comparing Flow Diverters to Adjunctive Stents. (29th July 2016) - Jankowitz, B; Iannaccone, F; De Santis, G; De Beule, M; Gounis, M; Van Der Marel, K; Puri, A
Abstract : Introduction: Historically, adjunctive stents had different constructions than flow diverters. The former were open- (e.g. Neuroform) or closed-cell (e.g. Enterprise) laser cut nitinol devices, with low metal-to-artery ratios and pore densities. The recent introduction of woven adjunctive stents (e.g. LVIS Jr., Leo Baby) blurred the line between adjunctive stents and flow diverters (e.g. Pipeline Embolization Device or PED). There is a misconception that woven adjunctive stents have flow diverting capabilities. A computational flow dynamic (CFD) model was used to compare the flow alteration effects of two adjunctive stents (Neuroform Atlas and LVIS Jr.) and one flow diverter (PED). Materials and methods: A CFD study was performed on a 2.6 mm sidewall aneurysm in a 2.2–2.3 mm diameter vessel. Three stents were modeled: Neuroform Atlas (3.0 × 24 mm), LVIS Jr. (3.5 × 20 mm), PED (2.75 × 10 mm). The stent was virtually deployed in a compliant vessel model with a wall thickness of 0.6 mm using Finite Element Analysis. For the flow conditions, stress free outlet was assumed with a steady state flow of 2.1 mL/s. Six CFD runs were performed on each adjunctive stent with varying degrees of rotation and placement. The following definitions were used; % aneurysm inflow = inflow rate/parent artery flow rate, turnover time = aneurysm volume/inflow rate, impact zone = area of aneurysm with WSS > 2 Pa. Two-sample T-tests compared Atlas to LVIS Jr. Results: The CFD study revealed that the 2 adjunctive stents did not divert a significant amount of flow when compared to a flow diverter (Table 1 ). When compared to each other, the average values for % aneurysm inflow (P = 0.265), turnover time (P = 0.960), and impact zone (P = 0.135) were not statistically different. In contrast, the PED significantly reduced % aneurysm inflow, turnover time, and impact zone. Conclusions: This analysis revealed that adjunctive stents do not divert flow significantly when compared to pre-treatment baselines. Only a flow diverter significantly altered the flow dynamics within the aneurysm. There was no statistically significant difference in the flow diversion capabilities between the two adjunctive stents. Disclosures: B. Jankowitz: None. F. Iannaccone: None. G. De Santis: None. M. De Beule: None. M. Gounis: None. K. Van Der Marel: None. A. Puri: None.